THE PERFORMANCE OF AGRICULTURAL EXTENSION IN DEVELOPING BALI COW BUSINESS IN MUNA REGENCY OF SOUTHEAST SULAWESI TENGGARA - Sari, A. M.; Nuraini, N. K.; Suparta, I. N. (E-Journal of Animal Science Udayana University, 2013)
The aims of this study is to know the performance of agricultural extension in term of developing Bali cow business and the success of farmers in developing Bali cow business in Muna regency. Those respondents in this study determined by classified random sampling by proportional technique namely 10% performance of agricultural extension taken by census. Based on result the agricultural extension categorize as good (69,13%), whereas the successful of farmer in term of Bali cow production categorized as less success (53,02%), There is unreal relationship between the performance of agricultural extension and success of farmer, whereas knowledge, skill, motivation, act, range of place of living relate real positive toward the performance of agricultural extension. Conclusions of this study are performance of agricultural extension workers in this area is included in good category, and success of farmer categorize as less success. Performance of agricultural extension relates unreal positive success of farmer. Whereas knowledge, skill, motivation, act, range of place of living relate real positive toward the performance of agricultural extension